Makna ummatan wasathâ Penafsiran Q.S Al-Baqarah : 143 : (Studi Komparatif Tafsir Klasik dan Kontemporer) - Ahmad Ramadhan; Adha Saputra; Alber Oki (ZAD Al-Mufassirin, 2020)
The selection of the above theme is intended to clearly explain the concept of being a middle ummah in accordance with the correct understanding. The preferred verse that is the object of research is Q.S. Al-Baqarah: 143. This research uses a literature study approach by analyzing the words of classical and contemporary interpretors and correcting the true words (tarjîh), as will be found the misappropriation of the meaning of the wasat ummatan itself. To find the truth that the theme above is very important to discuss, from this research will be able to know how the right concept of being a middle people can be a guide for every Muslim to live his life and also make every believer mentadaburi Al-'an Al-'Azhim.